Penerapan Strategi Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Prestasi Belajar Ekonomi Pada Siswa Kelas Xi Semester 2 Sma Negeri 1 Nawangan Kabupaten Pacitan Tahun Pelajaran 2014/2015 - NANDA ARIYANTO, HENDRAWAN (2016)
ABSTRACT STRATEGY IMPLEMENTATION OF COOPERATIVE LEARNING TYPE JIGSAW TO INCREASE ACHIEVEMENT ECONOMY IN CLASS XI SEMESTER 2 SMA STATE DISTRICT 1 Nawangan PACITAN LESSON YEAR 2014/2015 Hendrawan Nanda Ariyanto. A 210 060 125 Accounting Education Program . The Faculty of Education, University of Muhammadiyah Surakarta. 2015. The purpose of this study is to improve learning achievement of economic students with Jigsaw type of cooperative learning in class XI SMA Negeri 1 Nawangan the 2nd semester of the school year 2014/2015. This study uses classroom action research (PTK) with two cycles. Subjects in this study were students of class XI SMA Negeri 1 Nawangan, District Bandar, Pacitan in the 2nd half 2014/2015 subjects totaling 32 students. Data collection technique using tests and observation. Data were analyzed using analysis descriptive and comparative. The results showed that: Learning Jigsaw can improve learning achievement in the economy class XI B SMA Negeri 1 Nawangan second semester of academic year 2014/2015. Economics student learning achievement increased from 59.1 at baseline to 73.4 condition in the first cycle, then increased to 90.9 at the end of the second cycle. Keywords: achievement of learning, cooperative learning, jigsaw